2002
DOI: 10.1002/hep.1840360721
|View full text |Cite
|
Sign up to set email alerts
|

Role of liver biopsy in management of chronic hepatitis C: A systematic review

Abstract: This systematic review addresses 2 questions pertinent to the need for pretreatment liver biopsy in patients with chronic hepatitis C: how well do liver biopsy results predict treatment outcomes for chronic hepatitis C? How well do biochemical blood tests and serologic measures of fibrosis predict the biopsy findings in chronic hepatitis C? Medline and other electronic databases were searched from January 1985 to March 2002. Additional articles were sought in references of pertinent articles and recent journal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
92
1
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(100 citation statements)
references
References 70 publications
1
92
1
6
Order By: Relevance
“…Similar results have not been obtained with other diagnostic tests [10-17]. Since September 2002 these tests (FT-AT) have been used in several countries as an alternative to liver biopsy.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similar results have not been obtained with other diagnostic tests [10-17]. Since September 2002 these tests (FT-AT) have been used in several countries as an alternative to liver biopsy.…”
Section: Introductionsupporting
confidence: 70%
“…Among the non-invasive alternatives to liver biopsy [10], several studies have demonstrated the predictive value of two combinations of simple serum biochemical markers in patients infected with HCV: FibroTest (FT; Biopredictive, Paris, France; HCV-Fibrosure, Labcorp, Burlington, USA) for the assessment of fibrosis; and ActiTest (AT; Biopredictive, Paris, France) for the assessment of necroinflammatory activity (necrosis) [8,9,11-21]. Similar results have not been obtained with other diagnostic tests [10-17].…”
Section: Introductionmentioning
confidence: 99%
“…However, because of its invasiveness, liver biopsy cannot be performed frequently. In addition, there is a limitation in the accuracy of liver biopsy due to sampling error [11,12,13]. Thus, the development of noninvasive tests that are reliable, cost-effective and easy to use is required for evaluating the stage of hepatic fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…According to the latest consensus conferences, liver biopsy is still recommended in most patients [2,3]. However, recent studies strongly suggest that due to the limitations [4-6] and risks of biopsy [7], as well as the improvement of the diagnostic accuracy of biochemical markers [8,9], liver biopsy should no longer be considered mandatory.…”
Section: Introductionmentioning
confidence: 99%
“…Among the non-invasive alternatives to liver biopsy [9], numerous studies have demonstrated the predictive value of two combinations of simple serum biochemical markers in patients infected with HCV and HBV: FibroTest (FT) (Biopredictive, Houilles, France) for the assessment of fibrosis, and ActiTest (AT) (Biopredictive, Houilles, France) for the assessment of necroinflammatory activity [8,12-22]. Similar results have not been obtained by other diagnostic tests [9,12-14,16-22].…”
Section: Introductionmentioning
confidence: 99%